2018
DOI: 10.1186/s12944-018-0830-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasma apolipoprotein CIII, high sensitivity C-reactive protein and tumor necrosis factor-α contributes to the clinical features of coronary heart disease in Li and Han ethnic groups in China

Abstract: BackgroundApolipoprotein CIII (apoCIII) is an independent risk for coronary heart disease (CHD). In this study, we investigated the associations among plasma apoCIII, hs-CRP and TNF-α levels and their roles in the clinical features of CHD in the Li and Han ethnic groups in China.MethodsA cohort of 474 participants was recruited (238 atherosclerotic patients and 236 healthy controls) from the Li and Han ethnic groups. Blood samples were obtained to evaluate apoCIII, TNF-α, hs-CRP and lipid profiles. Chi-squared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Tumor necrosis factor- α (TNF- α ) was mainly produced by monocytes and macrophages. TNF- α was a pleiotropic inflammatory cytokine that promoted the proinflammatory response in coronary atherosclerosis and was also risk factor for coronary artery disease, and circulating TNF- α levels were related to increased risks of stable angina pectoris, unstable angina, and recurrent myocardial infarction [ 9 11 ]. TNF- α elicited inflammatory response via two receptors termed soluble TNF- α receptor-1 and 2 (sTNFR-1 and sTNFR-2).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor necrosis factor- α (TNF- α ) was mainly produced by monocytes and macrophages. TNF- α was a pleiotropic inflammatory cytokine that promoted the proinflammatory response in coronary atherosclerosis and was also risk factor for coronary artery disease, and circulating TNF- α levels were related to increased risks of stable angina pectoris, unstable angina, and recurrent myocardial infarction [ 9 11 ]. TNF- α elicited inflammatory response via two receptors termed soluble TNF- α receptor-1 and 2 (sTNFR-1 and sTNFR-2).…”
Section: Introductionmentioning
confidence: 99%
“…Under normal circumstances, the concentration of hs-CRP in plasma was in a stable state for a long period. After tissue damage in patients, hs-CRP concentration could rise rapidly and be detected in blood within 6–8 h and reached the peak at 24–48 h. [ 25 ]. Caselli C et al concluded that hs-CRP, as a marker of inflammation, is able to monitor the severity of disease and has high predictive accuracy for the development of coronary artery disease in patients with chronic chest pain [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia, hyperinsulinemia and IR can all cause disorders in lipid metabolism, oxidative stress toxicity and vascular endothelial damage, ultimately leading to the aggravation of coronary ATS [97]. As such, hyperlipidemia may contribute to the development of UA [98] while interactions between immune-inflammatory and atherogenic pathways may further contribute to UA [99]. However, in our study, IL-6 was not significantly increased in UA vs. ATS without UA, although our results agree with previous data, which reported that IL-6 (and TNF-α and CRP) levels are higher in UA patients than in healthy controls [100,101].…”
Section: Discussionmentioning
confidence: 99%